A monotongação dos ditongos orais decrescentes [aj], [ej], e [ow] na comunidade quilombola Conceição dos Caetanos do município de Tururu/CE - Freitas Neto, Raimundo Paula de (2024)
This study aims to investigate the variable phenomenon of monophthongization, which is the deletion of the glide in front of the falling oral diphthongs [aj], [ej], and [ow], as seen in caixa~caxa, beira~bera, and ouro~oro, in the oral speech of the quilombola community of Conceição dos Caetanos, in the municipality of Tururu/CE, from the theoretical- methodological perspective of Variationist Sociolinguistics (Weinreinch; Labov; Herzog, 2006; Labov, 2008). For this research, we based our work on the concepts of monophthong and monophthongization discussed by Trask (1996), Câmara Jr. (1997), Silva (2005), and Seara, Nunes, and Lazzarotto-Volcão (2011). It is important to highlight that the choice of this community was due to the fact that it was the first Afro-Brazilian community in the state of Ceará to be certified by the Fundação Cultural Palmares (FCP) as a Remnant Quilombo Community (CRQ), because of its significant socio-historical-cultural value, and for being located in the interior of the state, thus contributing to studies of Portuguese spoken in Ceará and, consequently, in Brazil. Regarding the methodological procedure, as this is a quantitative study, an oral corpus was composed of 31 surveys, divided into 12 social cells, stratified by structural variables such as preceding and following phonetic context, stressed syllable, word length, word class, and social variables like gender, age group, and education level, with 3 informants in each cell. In the first phase, we got to know the community and some local leaders. Subsequently, we met more community members to identify potential candidates for the study, and only after these initial contacts did we begin the interviews. The interviews were divided into two phases: the first was a sociolinguistic interview, followed by the application of a phonetic-phonological questionnaire based on the one from ALiB (2001). The selection of the interviewees followed specific criteria, as indicated by Tarallo (1985). The data were then stored on a personal computer and transcribed for analysis. It is important to note that the cell for men with 10 years or more of education and aged 55 or older was discarded as it did not have any informants that fit the cell’s profile. A total of 5672 occurrences of the studied diphthongs were extracted for statistical analysis, with the diphthong [ej] having the most occurrences in this study, totaling 2705 occurrences, about 47.70% of the total diphthongs. However, the diphthong that showed the highest proportion of its monophthongized form was [ow], with 31.1%, and we chose to use the computational program R (R Core Team, 2013). As a result, we confirmed almost all of our hypotheses: that the preceding and following environments directly condition the phenomenon of monophthongization, that syllable stress is one of the factors most influencing the high rate of monophthongization occurrences, that the length of the word directly conditions the suppression of diphthongs to transform them into monophthongs, and that the word class favors monophthongization. Regarding the social variables, our first hypothesis was confirmed, as we found that people with a higher age group exhibited more monophthongization in their usage proportions. Our second hypothesis was only refuted for the diphthong [ej], where men were more conservative. Our last hypothesis was confirmed regarding education level, as informants with higher education levels exhibited less monophthongization.